A formação dos graduandos do curso de letras – inglês e a implementação do programa Idiomas Sem Fronteiras - MORAES, Danielle de Sousa Bahury (2021)
Social relations were expanded from a phenomenon known as globalization that has been transforming the logic of social mobility about migratory flows, reducing borders and bringing individuals, languages and, consequently, cultures closer together. Thus, the need to master an international language and use new technologies has become more pressing in the 21st century in Brazil, with the aim of combining education that is not limited to national borders. The individuals that we will deal with are the undergraduates of the Arts – English course who need to have solid academic training to provide opportunities for English language knowledge for other undergraduates at the university to be able to carry out studies abroad. When discussing the formation of the English teacher, considering the historical, political and theoretical aspects, we resorted to bibliographical research based on: Nóvoa (1991; 2009), Tardif (2013), Libâneo (2006), Freire (1987; 1996), Saviani ( 2009) among others.The present analysis aimed to investigate didactic-methodological and linguistic proficiency limitations faced by students of the Arts/English Course in unresolved training in the space of their academic training that were directly related to the implementation of the Languages without Borders Program at the Federal University of Maranhão. In total, 09 subjects participated. With 7 undergraduates who taught English and 2 local coordinators, both from the afore mentioned program. Among the number of students, 6 were female and 1 male. The age range of those investigated was between 22 and 43. The data collection instrument was a semi-structured interview conducted through a script containing 19 questions. The results demonstrate that the subjects built a more consistent teaching identity, the fact that they participated in the IsF - English as teachers provided them with a different view of the Literature Course regarding the improvement of their methodological and linguistic proficiency deficiencies, the choice for profession was based on the aptitude for the English language and the permanence in the Course through the consolidation of pedagogical knowledge, which could be applied in loco; the constant contact with studies on and in the target language provided robust communicative skill and understanding and that graduation, in addition to being a possibility of knowledge legitimized by professional practice, is also strengthened when it unites pedagogical and linguistic skills in teacher education .